2018
DOI: 10.2337/dc18-0287
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Risk of Infections Among People With Type 1 or Type 2 Diabetes in a Large Primary Care Cohort Study

Abstract: Poor glycemic control is powerfully associated with serious infections and should be a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
234
3
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(269 citation statements)
references
References 30 publications
15
234
3
17
Order By: Relevance
“…13 Julia et al, also concluded that poor glycemic control is powerfully associated with serious infections in diabetic patients. 14…”
Section: Discussionmentioning
confidence: 99%
“…13 Julia et al, also concluded that poor glycemic control is powerfully associated with serious infections in diabetic patients. 14…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a well-established risk factor for infections, and the risk increases with poor glycemic control 6 . In general, glycated hemoglobin (HbA1c) >9% has been shown to be associated with 60% increased risk of severe bacterial pneumonia 7 .…”
Section: Diabetes Mellitus and Obesity Are Risk Factors For Severity mentioning
confidence: 99%
“…Analysis of patients with type 1 and type 2 diabetes enrolled in primary care in England have shown a clear increase in long-term risk of infection with increasing HbA1c [ 32 ]. In a population-based study from Denmark, individuals with HbA1c of 10.5% and above had hazards ratio of 1.64 for infections requiring hospitalization, compared to individuals with HbA1c between 5.50 and 6.49% [ 33 ].…”
Section: Effect Of Hyperglycemia and Glycemic Control On Infectionsmentioning
confidence: 99%